Factors Contributing to Gender Disparity in Education in Rural Areas: Evidence from Three Districts of Punjab, Pakistan - Luqman, Muhammad; Shahbaz, Babar; Shiewi , Xu; Wen, Yu (Journal of Development Policy Research and Practice (JoDPRP), 2017)
Education is an important human capital; and, it is the fundamental right of every human being irrespective of gender to acquire knowledge through education. Social scientists have highlighted the significance of female education without which socio-economic growth, especially in Asia, remains slow. However, gender disparity in education persists in rural peripherals of Pakistan, Afghanistan, Bhutan, India, Iran, Nepal and Bangladesh (UNESCO 2015). This deplorable situation is subject to multiple socio-economic and cultural barriers. In order to unveil these militating attributes, present investigation was conducted in three districts of the Punjab province in Pakistan from March to June 2016. The province is divided into three different zones: Northern, Central and Southern. From each zone, one district was purposively selected as the study area. From the selected districts (Sargodha, Khushab and Bhakhar), 100 rural households from each district were selected through multi-stage simple random sampling technique. The data were collected from 300 household heads and from their spouses through in-depth individual interviews to find out the difference in opinion of the male and female respondents. The collected data was analysed using SPSS. Paired t-test was used to find out the difference in responses of male and female respondents. In order to find out the difference in intensity of factors in the three districts, F-test was applied. Results showed that there is highly significant difference between age of male family heads and their spouses (wives) (χ2=50.121 and P<0.05). Similar trend was found in educational status of male heads and their spouses. Cross tabulation indicated that educational status of wives was low as compared to their husbands. Analysis showed that a number of socio-economic factors are responsible for the existing gender disparity with reference to education in the study areas. Respondents identified low income, high educational expenditures, low educational level of parents (especially the mother), and security concerns of parents regarding sexual harassment as the major factors impeding female education. Results of the F-test showed that there exists difference in intensity of factors in the three study districts of Punjab which contribute towards gender disparity in education. Highest intensity (x =2.74/3.00) was found in district Bhakhar as it is a remote district of Punjab with higher poverty rate, followed by district Khushab and Sargodha. It is recommended that the Government at the national level should take serious steps in creating conducive environment to enhance female enrolment rate in rural localities. The scope of this article is related to the following SDG / SDGs.